Photo Editing - Ricky Telg (EDIS)
WC096, a 4-page fact sheet by Ricky Telg, explains how to take good photographs and make them look even better through photo editing. Includes additional sources of information. Published by the UF Department of Agricultural Education and Communication, July 2010.